2018
DOI: 10.1186/s12950-018-0189-4
|View full text |Cite
|
Sign up to set email alerts
|

Caspase recruitment domain (CARD) family (CARD9, CARD10, CARD11, CARD14 and CARD15) are increased during active inflammation in patients with inflammatory bowel disease

Abstract: BackgroundThe CARD family plays an important role in innate immune response by the activation of NF-κB. The aim of this study was to determine the gene expression and to enumerate the protein-expressing cells of some members of the CARD family (CARD9, CARD10, CARD11, CARD14 and CARD15) in patients with IBD and normal controls without colonic inflammation.MethodsWe included 48 UC patients, 10 Crohn’s disease (CD) patients and 18 non-inflamed controls. Gene expression was performed by RT-PCR and protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
0
20
0
1
Order By: Relevance
“…CARMA3 is a member of the membrane-associated guanylate kinase (MAGUK) superfamily which acted as scaffold proteins. There are other two members in MAGUK family, CARMA1 and CARMA2[4]. All three proteins contained caspase recruitment domain, were known CARD11, CARD14 and CARD10, respectively[5].…”
Section: Introductionmentioning
confidence: 99%
“…CARMA3 is a member of the membrane-associated guanylate kinase (MAGUK) superfamily which acted as scaffold proteins. There are other two members in MAGUK family, CARMA1 and CARMA2[4]. All three proteins contained caspase recruitment domain, were known CARD11, CARD14 and CARD10, respectively[5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, we found that CARD10 was associated with inflammation by regulating NF‐κB activation and antiviral IFN signalling, and it was also reported to be involved in antiviral innate immune responses and DNA damage responses . In addition, CARD10 is critical for allergic airway inflammation and might be involved in IBD pathophysiology . The results suggest that CARD10 may play an important role in the progression of periodontitis inflammation.…”
Section: Discussionmentioning
confidence: 77%
“…37,38 In addition, CARD10 is critical for allergic airway inflammation and might be involved in IBD pathophysiology. 37,39 The results suggest that CARD10 may play an important role in the progression of periodontitis inflammation.…”
Section: Discussionmentioning
confidence: 90%
“…The medication directly treats inflammation of the large intestine.rectal foam-a foamy substance the person puts into the rectum like an enema [17]‫۔‬The medication directly treats inflammation of the large intestine.,suppository-a solid medication the person inserts into the rectum to dissolve. The intestinal lining absorbs the medication [18].Some people will need surgery to treat their ulcerative colitis when they have:colon cancer,dysplasia, or precancerous cells in the colon,complications that are life threatening, such as megacolon or bleeding,no improvement in symptoms or condition despite treatment,continued dependency on steroids.side effects from medications that threaten their health [19].Removal of the entire colon, including the rectum, "cures" ulcerative colitis. A surgeon performs the procedure at a hospital [20] A surgeon can perform two different types of surgery to remove a patient's colon and treat ulcerative colitis:proctocolectomy and ileostomy,proctocolectomy and ileoanal reservoir,Full recovery from both operations may take 4 to 6 weeks.,Eating, Diet, and Nutrition.Researchers have not found that eating, diet, and nutrition play a role in causing ulcerative colitis symptoms.…”
Section: Discussionmentioning
confidence: 99%